Rapid and user-friendly open-source CRISPR/Cas9 system for single- or multi-site editing of tomato genome. Issue 1 (1st January 2019) - Hu, Nan; Xian, Zhiqiang; Li, Ning; Liu, Yudong; Huang, Wei; Yan, Fang; Su, Deding; Chen, Jingxuan; Li, Zhengguo
Abstract: CRISPR/Cas9-induced genome editing is a powerful tool for studying gene function in a variety of organisms, including plants. Using multi-sgRNAs to target one or more genes is helpful to improve the efficacy of gene editing and facilitate multi-gene editing. Here, we describe a CRISPR/Cas9 system which can be conveniently developed as a CRISPR kit. SgRNA expression cassettes can be rapidly generated by one-step PCR using our CRISPR kit. In our kit, there are two binary vectors pHNCas9 and pHNCas9HT. The binary vector pHNCas9 was constructed to allow to assemble up to eight sgRNA expression cassettes by one-step Golden Gate cloning. Another binary vector pHNCas9HT can be used to generate a large number of single target constructs by directly transforming ligation reactions products into A. tumefaciens without several procedures, such as PCR and plasmid extraction. The two binary vectors are designed according to the principles of standard BioBrick assembly to be used as an open-source tool. For example, we used BioBrick as a visual T-DNA tag. We also developed a primer design aid to complement the system. With this primer design aid, researchers can rapidly obtain primers and GC content, and sgRNA sequence of target site. Our CRISPR/Cas9 system can perform single- and multi-site editing and multiple gene editing to produce various types of mutations in tomato. This rapid and user-friendly CRISPR/Cas9 system for tomato can be potentially used for mutagenesis of important crop species for genetic improvement and is suitable for research into the function of genes. Genetic engineering: Quick and easy CRISPR in tomato: Researchers in China have created a toolkit to easily mutate genes in tomato using the CRISPR gene modification technology. Zhengguo Li of Chongqing University developed the system in response to the lack of an open, standardized, reliable gene editing tool in tomato. The toolkit is designed according to an open-source, modular standard known as Biobrick. It consists of several molecular building blocks which can be used to target up to eight genes for editing or deletion. The kit also includes software to help researchers determine the DNA sequences necessary to copy genes of interest and prepare them for the CRISPR reactions. Li's team tested the toolkit by using it to successfully simultaneously mutate multiple genes involved in tomato ripening. The new toolkit will enable researchers to rapidly and easily manipulate genes in this important crop.